2018
DOI: 10.1111/chso.12271
|View full text |Cite
|
Sign up to set email alerts
|

Adolescents’ Perspectives on Personal and Societal Responsibility for Childhood Obesity — The Study of Beliefs through ‘Serious’ Game (PlayDecide)

Abstract: The dominant approaches to public health policy on childhood obesity are based on the neoliberal emphasis of personal choice and individual responsibility. We study adolescents' (N = 81) beliefs about responsibility for childhood obesity as a public health issue, through an innovative participatory method, PlayDecide, organised in two countries: the UK and Spain. There is no evidence of a blanket rejection of individual responsibility, rather, a call for renegotiation of the values that inform adolescents' foo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 35 publications
2
8
0
Order By: Relevance
“…According to previous studies, adolescents perceived alcohol to be even more harmful than cannabis [ 40 ]. However, the reasons our participants gave for using alcohol were also in line with other studies [ 14 , 15 , 16 ]. These included belonging to a group, regulating and controlling their emotions, having new experiences and excitement.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…According to previous studies, adolescents perceived alcohol to be even more harmful than cannabis [ 40 ]. However, the reasons our participants gave for using alcohol were also in line with other studies [ 14 , 15 , 16 ]. These included belonging to a group, regulating and controlling their emotions, having new experiences and excitement.…”
Section: Discussionsupporting
confidence: 90%
“…These included belonging to a group, regulating and controlling their emotions, having new experiences and excitement. Research has found that some adolescents had not considered the harmful consequences of alcohol use at all [ 41 ] and did not feel they were responsible for them [ 15 ]. Instead, adolescents said that some adolescents seemed to feel that seeking new experiences could be more important than having a good relationship with their parents.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…All girls struggled to some extent with gaining a 'perfect' body, which is in line with many studies about body image and bodyweight among adolescent girls (Megalakaki et al, 2013;Stevenson et al, 2007;Stigler et al, 2011). The need for unhealthy food for social belonging on the one hand while worrying about unhealthy choices on the other hand was also found by Timotijevic et al (2018). This worrying about bodyweight can be explained by the current obesity discourse which tends to medicalise obesity and includes neo-liberal views on health, including a focus on self-regulation, own responsibility and autonomy (Lawrence, 2004;Lupton, 2013;Rich and Evans, 2005).…”
Section: Discussionsupporting
confidence: 82%